Contracting in Japan : the bargains people make when information is costly, commitment is hard, friendships are unstable, and suing is not worth it / J. Mark Ramseyer. - Ramseyer, J. Mark, 1954- (Cambridge studies in economics, choice, and society., 2023)
Economic arrangements, Ramseyer writes, are structured and implemented with the intent and hope that they will be carried out with 'care, intelligence, discretion, and effort'. Yet entrepreneurs work with partial information about the products, and people, they are dealing with. 'Contracting in Japan' illustrates this by examining five sets of negotiations and unusual contractual arrangements among non-specialist businessmen, and women, in Japan. In it, Ramseyer explores how sake brewers were able to obtain and market the necessary, but difficult-to-grow, sake rice that captured the local terroir; how Buddhist temples tried to compensate for rapidly falling donations by negotiating unusual funerary contracts; and how pre-war local elites used leasing instead of loans to fund local agriculture.